ANALYSIS OF FACTORS THAT INFLUENCE CONSUMER DECISIONS TO SHOP AT BALTINI INTERNATIONAL - -, Jesslyn (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2022)
This study aims to determine the level of purchasing decisions of consumers from the influence of service quality and trust in Baltini, so that the analysis is carried out on Baltini site users. The method to be used is quantitative method, using secondary data sources. Information will be analyzed with descriptive quantitative analysis obtained using a questionnaire instrument. The sampling technique uses purposive sampling. The research indicators use a Likert scale to obtain conclusions from the research. Then the data collected related to the object under study is analyzed based on the respondents' responses obtained using the slovin formula. The results of this study were obtained through data processing results. In this study includes multiple regression analysis.